Strategies in designing user interface for a microsoft multipoint-based courseware - Jamaludin, Zulikha (International Association of Technology, Education and Development (IATED), 2010)
Designing interaction in a courseware has been an ongoing challenge worldwide, especially now,after the introduction of Microsoft Multipoint SDK (Multipoint). This new feature enables multiple,up to 250, USB mouse devices to work simultaneously on one computer. Previous design of courseware interface only takes one mouse into account. Now interface designers have to consider 1 to 250 mouse devices, which in turn results in similar number of pointers or cursors scattering all over in the display. This paper table the impact of Multipoint feature in a courseware interface design and suggests ways to handle multiple pointers on screen while, at the same time, still complying to the user interface guidelines. Utilizing a Multipoint-based courseware that we developed internally, we offer three strategies that can be adopted for a group of 2-4 pointers, 5-10 pointers, and more than ten pointers. These strategies are tested by a group of university students and we found out that the strategy helps providing smooth interaction and collaboration for up to 15 users and 15 pointers on a single display. Details of the results is reported in the paper.